2010
DOI: 10.1016/j.sbspro.2010.07.288
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction, spirituality well-being and hope in cancer patients

Abstract: Background: The older adults are a part of society whose population is increasing as science progresses and health conditions improve. Social, psychological and behavioral factors will be influenced on life satisfaction in older adults. We aimed to predictive role of psychosocial factors in life satisfaction older adults. Methods: It was a descriptive-analytical study which has conducted on 679 older adults through convenience sampling from Qom city during 2018. The data were collected using demographic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 17 publications
8
27
1
3
Order By: Relevance
“…The results of the present study indicate that participants had relatively high levels of hope and are consistent with previous Iranian studies ( Abdullah-Zadeh et al, 2011;Pourghaznein et al, 2003;Aghahosseini et al, 2012;Jafari et al, 2010) and studies in other countries wherein cancer patients had moderate to high levels of hope (Reynolds, 2008;Utne et al, 2008). Iranian cancer patients have contributed this high degree of hope to the non-disclosure of cancer-related information, health care providers and relatives' indications that their cancer was potentially curable, belief in a miracle cure, religious resources, and the lessening of cancer symptoms following initial treatment .…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study indicate that participants had relatively high levels of hope and are consistent with previous Iranian studies ( Abdullah-Zadeh et al, 2011;Pourghaznein et al, 2003;Aghahosseini et al, 2012;Jafari et al, 2010) and studies in other countries wherein cancer patients had moderate to high levels of hope (Reynolds, 2008;Utne et al, 2008). Iranian cancer patients have contributed this high degree of hope to the non-disclosure of cancer-related information, health care providers and relatives' indications that their cancer was potentially curable, belief in a miracle cure, religious resources, and the lessening of cancer symptoms following initial treatment .…”
Section: Discussionsupporting
confidence: 93%
“…In this sense, hope is an important feeling during the confrontation with the disease process and individual well-being, (1) being crucial to maintain feelings of usefulness and affection for those around. For these patients, the achievement of the desired levels of hope is founded on a desire to live and to return to a healthy life, besides the desire to maintain ties of affection and attention, especially with the closest people.…”
Section: Discussionmentioning
confidence: 99%
“…Hope can be defined as a subjective probability of good outcomes, (1) representing the feeling of an optimistic future for men, which allows for the establishment of plans and long-term goals. (2) In the face of daily situations, people tend to anchor their hope in issues that are significant to them, either external, such as family, friends or something supernatural; as well as internal, when people deposit their hopes on themselves, thinking about their life and the possibility of personal achievements.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Asaroudi on nursing staff and the study by Jafari on patients with cancer, there was a significant relationship between the existential and religious dimensions and the overall dimension of spiritual well-being and life satisfaction (7,9). Kalantar et al (19), found a significant relationship between spiritual well-being and life satisfaction in girls.…”
Section: Life Satisfactionmentioning
confidence: 95%
“…Spiritual well-being consists of two dimensions; first, the religious dimension, which refers to the relationship with God, and second, the existential well-being, which refers to individuals' feelings, what they do, why they do it and to where they belong (7).…”
Section: Introductionmentioning
confidence: 99%